Analysis of the phosphoproteome of CK2α(-/-)/Δα′ C2C12 myoblasts compared to the wild-type cells - Borgo, Christian; Cesaro, Luca; Hirota, Tsuyoshi; Kuwata, Keiko; D'Amore, Claudio; Ruppert, Thomas; Blatnik, Renata; Salvi, Mauro; Pinna, Lorenzo A. (Open biology, 2023)
CK2 is a Ser/Thr protein kinase composed of two catalytic (α/α′) subunits and a non-catalytic β-subunit dimer, whose activity is often abnormally high in cancer cells. The concept that CK2 may be dispensable for cell survival has been challenged by the finding that viable CK2α/α′ knock-out myoblast clones still express small amounts of an N-terminally deleted α′ subunit generated during the CRISPR/Cas9 procedure. Here we show that, although the overall CK2 activity of these CK2α(-/-)/Δα′ (KO) cells is less than 10% compared to wild-type (WT) cells, the number of phosphosites with the CK2 consensus is comparable to that of WT cells. A more in-depth analysis, however, reveals that the two phosphoproteomes are not superimposable according to a number of criteria, notably a functional analysis of the phosphoproteome found in the two types of cells, and variable sensitivity of the phosphosites to two structurally unrelated CK2 inhibitors. These data support the idea that a minimal CK2 activity, as in KO cells, is sufficient to perform basic housekeeping functions essential for cell survival, but not to accomplish several specialized tasks required upon cell differentiation and transformation. From this standpoint, a controlled downregulation of CK2 would represent a safe and valuable anti-cancer strategy.
Im Text ist "-" jeweils hochgestellt
Gesehen am 14.04.2023